EXTREME TOURISM IN UZBEKISTAN (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The development and peculiarities of extreme tourism in Uzbekistan, including unique natural places and opportunities for active recreation are considered. Popular types of extreme entertainment offered by the country and their impact on the tourism industry are analyzed. The study also focuses on the infrastructure and safety of extreme tourism in Uzbekistan, including the availability of appropriate equipment and trained instructors. Measures for sustainable development of this segment of tourism are analyzed, taking into account environmental aspects. In conclusion, the potential of Uzbekistan as an attractive destination for lovers of active recreation, contributing to the diversity of tourist experiences is emphasized.